Method for preparing composite coagulant by multi-source solid waste collaborative staged extraction and cascade utilization

CN122979633APending Publication Date: 2026-10-27HENAN FLUORINE BASED NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611236032.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0012]本发明目的在于解决现有技术中铝加工及新能源行业多种固废/废液处置难度大、资源化利用率低、高价值元素与低价值元素混杂处理导致处理成本高的问题,提供一种多源固废协同分阶提取与梯级利用制备复合混凝剂的方法

Benefits of technology

1.多源固废协同处置:将赤泥、大修渣、含氟盐酸、磷酸铁锂提锂渣、铝电解质废料、锂云母渣、锂电池回收铁铝渣等多类固废/废液纳入统一的处理体系,实现多源废弃物的系统性协同处置。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to solid waste resource utilization and wastewater treatment technical field, and relates to a method for preparing composite coagulant by multi-source solid waste collaborative step-by-step extraction and cascade utilization, wherein low-fluorine hydrochloric acid or sulfuric acid is used for acid leaching of lithium-containing solid waste, and lithium-containing leaching solution and lithium extraction residue are obtained by filtration; the lithium extraction residue is mixed with fluorine-containing materials and calcium source for reaction, so that fluorine ions are precipitated and separated in the form of calcium fluoride, and calcium fluoride and fluorine removal mixed solution are obtained by filtration; the fluorine removal mixed solution is mixed with iron and aluminum-containing solid waste, sulfuric acid is additionally added, and reaction is carried out under the conditions of stirring and aeration, and composite coagulant solution is obtained by filtration. The method realizes systematic collaborative disposal of multi-source waste, preferentially extracts high-value lithium resources, secondly recovers calcium fluoride by-product, and finally prepares low-value iron and aluminum components into composite coagulant, so that step-by-step separation and high-value utilization of each component are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization and wastewater treatment technology, specifically to a method for preparing composite coagulants through synergistic and tiered extraction and utilization of multi-source solid waste. Background Technology

[0002] The aluminum processing and new energy industries generate a large amount of solid waste annually, which mainly includes the following categories: (1) Red mud: A highly alkaline solid waste generated during the production of alumina. Approximately 1.0 to 2.0 tons of red mud are generated for every ton of alumina produced. Red mud contains abundant elements such as iron and aluminum, but due to its high alkalinity, fine particle size, and high water content, it is difficult to utilize as a resource and is currently mainly stored in the open air.

[0003] (2) Aluminum electrolysis overhaul slag: A mixture of waste cathode carbon blocks, refractory bricks, electrolytes, etc., generated during the overhaul of aluminum electrolysis cells. Fluorides account for about 35%, graphitic carbon accounts for about 30%, and valuable elements such as lithium (grade can reach more than 0.3%) are also present. It is classified as hazardous waste. Existing technologies have methods for extracting lithium from overhaul slag by acid leaching, with a lithium extraction rate of more than 90%.

[0004] (3) Fluorine-containing hydrochloric acid waste liquid: generated during the production of lithium hexafluorophosphate. Every ton of lithium hexafluorophosphate produces 3.5 to 5.5 tons of fluorine-containing hydrochloric acid as a byproduct. It has a high concentration of fluoride ions and strong acidity, making it difficult to treat. Existing continuous defluorination technology can reduce the fluorine mass concentration in hydrochloric acid from 55 g / L to 11 g / L.

[0005] (4) Lithium extraction residue from waste lithium iron phosphate cathode material: The phosphorus iron residue remaining after selective lithium extraction during the recycling process of lithium iron phosphate batteries is mainly composed of FePO4, and there is currently no effective treatment method.

[0006] (5) Lithium-containing waste aluminum electrolyte: waste electrolyte generated during aluminum electrolysis, with a lithium content of 1% to 3% and a large amount of fluoride.

[0007] (6) Lithium extraction slag from lepidolite: The leaching slag produced during the lithium extraction process of lepidolite sulfate roasting mainly consists of SiO2, Al2O3 and CaO. Among them, the Fe(OH)3 content in the neutralized and impurity-removed slag from lepidolite is about 5%~10%, and the Al(OH)3 content is about 25%~40%.

[0008] (7) Iron and aluminum slag from lithium battery recycling: The amount of secondary waste containing iron and aluminum generated during the recycling of ternary lithium batteries is huge.

[0009] Currently, most of the aforementioned solid wastes / liquids are treated separately or simply stored, which presents the following problems: First, the treatment technologies for each waste are scattered, lacking a systematic and coordinated disposal plan; second, the mixed treatment of high-value elements (lithium, fluorine) and low-value elements (iron, aluminum) leads to high treatment costs; and third, the iron and aluminum residues after lithium extraction lack high-value utilization pathways, resulting in a significant risk of secondary pollution.

[0010] Existing technologies have attempted to co-treat red mud and waste cathodes (e.g., CN201910032015.9, a method for resource utilization of high-speed iron red mud and waste cathodes through co-treatment), achieving iron reduction and fluoride volatilization through high-temperature sintering; there are also methods for the joint recovery of waste lithium iron phosphate and iron-aluminum slag (e.g., CN118833787A, a carbon reduction and emission reduction joint recovery method of waste lithium iron phosphate and iron-aluminum slag), using an acid solution from iron-aluminum slag as a leaching agent to extract lithium. However, these technologies are still limited to a combination of single or two types of waste and have failed to achieve systematic co-treatment of multi-source solid waste.

[0011] Therefore, there is an urgent need for a method to prepare composite coagulants through the synergistic, staged extraction and cascade utilization of multi-source solid waste to solve the above-mentioned technical problems. Summary of the Invention

[0012] The purpose of this invention is to solve the problems of high difficulty in disposing of various solid wastes / waste liquids in the aluminum processing and new energy industries, low resource utilization rate, and high treatment costs caused by the mixed treatment of high-value and low-value elements in the existing technology. The invention provides a method for the synergistic and tiered extraction and utilization of multi-source solid wastes to prepare composite coagulants.

[0013] This invention is implemented according to the following technical solution: A method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste includes the following steps: S1, One-time leaching for lithium extraction: Low-fluoride hydrochloric acid or sulfuric acid is used to acidically leach lithium-containing solid waste, selectively extracting lithium elements, and filtering to obtain lithium-containing leachate and lithium extraction residue. S2, Secondary fluoride removal and fluoride extraction: The lithium extraction residue from step S1 is mixed and reacted with fluorine-containing materials and calcium source to precipitate and separate fluoride ions in the form of calcium fluoride. The mixture is then filtered to obtain calcium fluoride and fluoride removal solution. S3, preparation of coagulant by three acid leaching steps: the defluorinated mixture obtained in step S2 is mixed with iron and aluminum-containing solid waste, sulfuric acid is added, and the mixture is reacted under stirring and aeration conditions. The mixture is then filtered to obtain a composite coagulant solution.

[0014] Preferably, in step S1, the fluorinated hydrochloric acid waste liquid is pretreated by reacting with a calcium source to obtain low-fluoride hydrochloric acid and calcium fluoride; the fluoride ion concentration in the obtained low-fluoride hydrochloric acid is ≤0.2 mol / L; the calcium source is one or both of calcium carbonate and calcium oxide materials.

[0015] Preferably, in step S1, the lithium-containing solid waste is one or more of the following: aluminum electrolysis overhaul slag, lithium-containing waste aluminum electrolyte, lithium extraction slag from lepidolite, waste lithium iron phosphate cathode material, and lepidolite neutralization and impurity removal slag.

[0016] Preferably, in step S1, the leaching conditions during acid leaching are: a liquid-to-solid ratio of 3:1 to 5:1, with the unit of liquid-to-solid ratio being L:kg; a leaching temperature of 60 to 90°C; a leaching time of 2 to 4 hours; and a final leaching pH of 1.5 to 2.5.

[0017] Preferably, in step S2, the fluorine-containing material is one or more of fluorine-containing hydrochloric acid waste liquid, aluminum electrolysis overhaul slag, and lithium-containing waste aluminum electrolyte; the calcium source is one or two of calcium carbonate materials and calcium oxide materials.

[0018] Preferably, in step S2, at least one of the following is added to the mixing reaction: red mud, waste lithium iron phosphate lithium extraction slag, and lithium battery recycled iron-aluminum slag.

[0019] Preferably, in step S2, during the mixing reaction, the reaction temperature is controlled at 60~90℃, the reaction time at 1~3 h, and the final pH at the reaction endpoint is 6~8.

[0020] Preferably, in step S3, the iron-aluminum-containing solid waste is selected from one or more of the following: red mud, lithium battery recycled iron-aluminum slag, lepidolite neutralization and impurity removal slag, and waste lithium iron phosphate extraction slag.

[0021] Preferably, during the reaction process in step S3 under stirring and aeration conditions, the reaction temperature is 80~100℃, the reaction time is 2~5 h, and the aeration pressure is 0.2~0.6 MPa.

[0022] Preferably, in step S1, the lithium-containing leachate is purified and precipitated to obtain lithium carbonate or lithium phosphate.

[0023] More preferably, in step S1, the lithium-containing leachate is purified and then precipitated with sodium carbonate to obtain a lithium carbonate product.

[0024] Preferably, the filter residue generated in each step is washed with water and then used for building materials or landfill. The washing liquid obtained after washing the filter residue is recycled to step S1 or step S3. When recycled, the concentration of fluoride ions in the washing liquid is controlled to not exceed 0.5 g / L.

[0025] In this invention, the purity of calcium fluoride is determined by fluoride ion selective electrode method or EDTA complexometric titration method; the content of Al2O3 and Fe2O3 in the composite coagulant solution is determined by inductively coupled plasma atomic emission spectrometry or EDTA complexometric titration method.

[0026] Specifically, the present invention includes the following steps: S1 First Stage: Lithium Extraction via Single Leaching Pretreatment of fluorinated hydrochloric acid waste liquid: Add calcium carbonate calcium source to fluorinated hydrochloric acid waste liquid, stir and react until the fluoride ion concentration in the solution drops to below 0.2 mol / L, filter to obtain calcium fluoride precipitate (which can be used as a by-product) and low-fluoride hydrochloric acid.

[0027] One or more lithium-containing solid wastes are mixed from aluminum electrolysis overhaul slag, lithium-containing waste aluminum electrolyte, lithium extraction slag from lepidolite, waste lithium iron phosphate cathode material, and lepidolite neutralization and impurity removal slag. Acidic leaching with the aforementioned low-fluoride hydrochloric acid or sulfuric acid is then performed to selectively extract lithium. The leaching conditions are: liquid-to-solid ratio (volume-to-mass ratio, L / kg) 3:1~5:1, leaching temperature 60~90℃, leaching time 2~4 h, and final pH controlled at 1.5~2.5. Filtration yields a lithium-containing leachate and lithium extraction residue. The lithium-containing leachate is then purified and precipitated to obtain lithium carbonate or lithium phosphate products.

[0028] S2 Second Stage: Secondary Defluorination and Fluorine Removal The lithium extraction residue generated in step S1 is mixed with one or more of the following: fluorinated hydrochloric acid waste liquid (untreated portion), red mud, waste lithium iron phosphate lithium extraction slag, aluminum electrolysis overhaul slag, lithium-containing waste aluminum electrolyte, and lithium battery recycled iron-aluminum slag. A calcium source (calcium carbonate or calcium oxide) is added, and the reaction temperature is controlled at 60-90℃ for 1-3 hours, with a final pH of 6-8. This allows fluoride ions to precipitate and separate as calcium fluoride. Filtration yields calcium fluoride byproduct (purity ≥95%) and a defluorinated mixture. The purity of calcium fluoride is determined using a fluoride ion selective electrode method or EDTA complexometric titration.

[0029] S3 Third Stage: Preparation of Coagulant through Three Acid Leakage Stages The defluorinated mixture generated in step S2 is mixed with one or more of the following: red mud (unused portion), lithium battery recovery iron-aluminum slag, lepidolite neutralization and impurity removal slag (iron-aluminum residue after lithium extraction), and waste lithium iron phosphate extraction slag. Sulfuric acid is added, and the mixture is reacted under stirring and aeration conditions at a temperature of 80-100℃ for 2-5 hours and an aeration pressure of 0.2-0.6 MPa. This process allows iron and aluminum elements to fully dissolve and form polynuclear hydroxyl complexes. The mixture is then filtered to obtain a composite coagulant solution. The contents of Al2O3 and Fe2O3 in the coagulant solution are determined using inductively coupled plasma optical emission spectrometry (ICP-OES) or EDTA complexometric titration.

[0030] Washing liquid reuse: The filter residue generated in each step is washed with water. The washing liquid mainly contains small amounts of acid and soluble salts, with a pH of approximately 2-5. After collection, the washing liquid can be reused in the first-stage fluoride-containing hydrochloric acid pretreatment step (for dilution or acid replenishment), or reused in the third stage as makeup water, depending on its acidity and composition. When reusing, the fluoride ion concentration in the washing liquid must be controlled to not exceed 0.5 g / L to avoid affecting subsequent steps. The specific reuse method is as follows: pump the washing liquid into the corresponding reaction vessel, mix it with the raw materials, and simultaneously add fresh acid or alkali to adjust the pH value according to the target pH value.

[0031] The material flow between each step can be flexibly adjusted based on raw material availability and the target product. The amount of acid added in each step is a partial dissolution amount; in actual production, the amount of acid can be adjusted according to the requirements of the target product to control the dissolution rate and product composition.

[0032] The reaction principles involved in the above process are as follows: First stage: Fluorine-containing hydrochloric acid pretreatment for fluoride removal: 2HF + CaCO3→ CaF2↓ + CO2↑ + H2O; CaCl2+ 2HF → CaF2↓ + 2HCl; First stage: Selective lithium extraction (using low-fluoride hydrochloric acid or sulfuric acid): In acidic conditions, lithium preferentially dissolves from lithium-containing solid waste. Li2O + 2H + → 2Li + + H2O; LiAlSi2O6+ 4H + → Li + + Al 3+ + 2SiO2 + 2H2O; After purification, the lithium-containing leachate is precipitated with sodium carbonate: 2Li + + Na₂CO₃→ Li₂CO₃↓ + 2Na + ; Second stage: Fluorine removal and purification Fluoride ions in fluorine-containing materials react with calcium sources to form calcium fluoride precipitate: 2HF + CaCO3→ CaF2↓ + CO2↑ + H2O; CaCl2+ 2HF → CaF2↓ + 2HCl; Na3AlF6 + 3CaO + 6H + → 3CaF2↓ + Al 3+ + 3Na + + 3H2O; Third stage: Iron and aluminum leaching and formation of composite coagulants: Alumina and ferric oxide in red mud and iron-aluminum slag dissolve under acidic conditions: Al2O3+ 6H + → 2Al 3+ + 3H2O; Fe2O3+ 6H + → 2Fe 3+ + 3H2O; FePO4+ 3H + → Fe 3+ + H3PO4; Under aeration conditions, Fe 2+ Oxidized to Fe 3+ : 4Fe 2+ + O2 + 4H + → 4Fe 3+ + 2H2O; Al 3+ Fe 3+ Hydrolytic polymerization occurs in solution, forming polynuclear hydroxyl complexes: Al 3+ + nH2O → [Al(OH) n ] (3-n)+ + nH + ; Fe 3+ + nH2O → [Fe(OH) n ] (3-n)+ + nH + ; Ultimately, a composite coagulant solution containing multiple metals such as aluminum and iron is formed.

[0033] This invention synergistically treats various solid wastes / waste liquids, including aluminum electrolysis overhaul slag, red mud, fluorine-containing hydrochloric acid waste liquid, lithium battery recycling waste, aluminum electrolyte waste, and lithium extraction slag from lepidolite. It extracts elements such as lithium and fluorine in stages and uses the residual iron and aluminum components after extraction to prepare a composite coagulant.

[0034] Beneficial effects: 1. Co-processing of multi-source solid waste: Integrating various types of solid waste / waste liquid, such as red mud, overhaul slag, fluorinated hydrochloric acid, lithium iron phosphate extraction slag, aluminum electrolyte waste, lepidolite slag, and lithium battery recycling iron and aluminum slag, into a unified treatment system to achieve systematic and co-processing of multi-source waste.

[0035] 2. Step-by-step extraction and tiered utilization: Following the step-by-step processing sequence of "first extracting lithium → then removing fluoride → finally preparing coagulant", high-value lithium resources are extracted first, followed by the recovery of calcium fluoride by-products, and finally the low-value iron and aluminum components are prepared into composite coagulant, realizing the step-by-step separation and high-value utilization of each component.

[0036] 3. Waste-to-waste treatment and process synergy: The free acid in the fluorine-containing hydrochloric acid waste liquid is used as a lithium extraction leaching agent after pretreatment to remove fluoride, avoiding the formation of lithium fluoride precipitate by fluoride ions, which would affect the lithium recovery rate; the fluoride in the lithium extraction residue is converted into calcium fluoride product in the defluorination step, realizing the resource recovery of fluoride.

[0037] 4. Full component resource utilization: The residues generated in each step can be used for building materials or landfill after being washed with water, and the washing liquid is recycled into the system, realizing the full component resource utilization of solid waste / waste liquid. Detailed Implementation

[0038] The present invention will be further described below with reference to specific embodiments. The illustrative embodiments and descriptions herein are used to explain the present invention, but are not intended to limit the present invention.

[0039] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0040] There are no particular restrictions on the purity of any of the raw materials used in this invention; however, it is preferred to use materials with conventional purity levels used in the field.

[0041] Unless otherwise specified, the apparatus used in this invention employs commonly used devices in the field.

[0042] In the following examples and comparative examples: the fluorinated hydrochloric acid waste liquid contains 15% HCl and 5% HF by mass; the aluminum electrolysis overhaul slag contains 0.35% lithium and about 35% fluoride; and the red mud contains 30% water, about 18% Al2O3 and about 25% Fe2O3.

[0043] Example 1 (using red mud, aluminum electrolysis overhaul slag, and fluorine-containing hydrochloric acid as main raw materials) A method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste includes the following steps: Pretreatment of fluorinated hydrochloric acid: Take 800 kg of fluorinated hydrochloric acid waste liquid (HCl mass fraction 15%, HF mass fraction 5%), of which approximately 40 kg (approximately 2 kmol) of HF is added, along with 50 kg (approximately 0.5 kmol) of building aggregate (CaCO3 content ≥90%). Stir and react for 1 h. Filter to obtain calcium fluoride precipitate (approximately 39 kg, purity determined by fluoride ion selective electrode method to be 96.2%) and low-fluoride hydrochloric acid (F... -Concentration ≤ 0.1 mol / L, measured 0.08 mol / L.

[0044] S1 (Single-step leaching for lithium extraction): Take 500 kg of aluminum electrolysis overhaul residue (lithium grade 0.35%, fluoride content approximately 35%), crush and grind it to 100% -0.1 mm (all particles are less than 0.1 mm in diameter), add the aforementioned low-fluorine hydrochloric acid, control the liquid-to-solid ratio at 4:1 (L / kg), leaching temperature at 80℃, stirring speed at 120 r / min, leaching time at 3 h, and final pH=2.0. Filter to obtain lithium-containing leachate and lithium extraction residue. After impurity removal and concentration, add sodium carbonate to precipitate the lithium-containing leachate to obtain lithium carbonate product (purity determined by atomic absorption spectrometry is 98.2%, lithium recovery rate 85%).

[0045] S2 (Secondary Defluorination and Fluorine Removal): The lithium extraction residue from step S1 is mixed with 400 kg of red mud (30% moisture content, approximately 18% Al2O3 content, and approximately 25% Fe2O3 content) and 200 kg of building aggregate (≥90% CaCO3 content). The mixture is added to a reaction vessel, and 500 kg of fluoride-containing hydrochloric acid waste liquid is added. The mixture is stirred and reacted for 2 h, with the temperature controlled at 70℃. The pH is adjusted to 7.0±0.3 with lime milk. The mixture is filtered to obtain calcium fluoride precipitate (purity determined by EDTA complexometric titration method is 96.5%, yield is approximately 180 kg) and defluorination mixture.

[0046] S3 (Preparation of coagulant through three acid leaching steps): The defluorinated mixture from step S2 was mixed with 300 kg of red mud and 80 kg of concentrated sulfuric acid (98%). The mixture was heated to 90°C, stirred at 120 r / min, and aerated with compressed air (0.4 MPa pressure) for 3 h. The resulting composite coagulant solution was obtained by filtration, with a volume of approximately 1500 L. ICP-OES analysis showed that the Al2O3 content in the coagulant solution was 2.8 g / L, the Fe2O3 content was 3.2 g / L, and the total solids content was approximately 10%.

[0047] Washing solution reuse: Wash the filter residue twice with an equal mass of tap water, collect the washing solution, and measure the pH to be approximately 3.2. - The concentration is 0.2 g / L. This washing solution is reused in the first-stage hydrochloric acid pretreatment step to replace part of the tap water for diluting the hydrochloric acid, while a small amount of fresh gravel is added to maintain the defluorination effect.

[0048] Example 2 (using waste lithium iron phosphate cathode sheet crushed powder + lithium battery recycled iron and aluminum slag + fluorine-containing hydrochloric acid as main raw materials) A method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste includes the following steps: Pretreatment of fluorinated hydrochloric acid: Take 600 kg of fluorinated hydrochloric acid waste liquid (HCl mass fraction 15%, HF mass fraction 5%), add 50 kg of limestone powder, stir and react for 1 h, filter to obtain low-fluoride hydrochloric acid (F - Concentration 0.09 mol / L.

[0049] S1 (Single-step leaching for lithium extraction): Take 200 kg of crushed waste lithium iron phosphate cathode material (Li content approximately 4%, Fe content approximately 35%), add the above-mentioned low-fluorine hydrochloric acid, control the liquid-to-solid ratio at 4:1, leaching temperature at 75℃, stir and leach for 2.5 h, with a final pH of 1.8, filter to obtain lithium-containing leachate and lithium extraction residue (mainly FePO4). The lithium-containing leachate is purified and precipitated to obtain lithium carbonate product (lithium recovery rate 82%, purity 97.5%).

[0050] S2 (Secondary Defluorination and Fluorine Removal): The lithium extraction residue generated in step S1 is mixed with 300 kg of lithium battery recycled iron-aluminum slag (Fe content approximately 20%, Al content approximately 25%) and 150 kg of building aggregate. The mixture is added to a reaction vessel, and 400 kg of fluorine-containing hydrochloric acid waste liquid is added. The mixture is stirred and reacted for 2 h at a temperature of 65℃. The pH is adjusted to 7.0±0.3 with lime milk. The mixture is filtered to obtain calcium fluoride precipitate (purity 95.8%) and defluorinated mixture.

[0051] S3 (Preparation of coagulant through three acid leaching processes): The defluorinated mixture generated in step S2 was mixed with 200 kg of lithium battery recycled iron-aluminum slag and 60 kg of concentrated sulfuric acid. The mixture was heated to 90°C and aerated for 3 h at an aeration pressure of 0.2 MPa. The resulting composite coagulant solution was obtained by filtration. The Al2O3 content was determined to be 3.1 g / L, and the Fe2O3 content was 2.9 g / L.

[0052] Example 3 (using lithium mica residue + electrolyte waste + red mud as main raw materials) A method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste includes the following steps: S1 (Single-step leaching for lithium extraction): Take 800 kg of neutralized and impurity-removed lepidolite residue (Li₂SO₄ content approximately 2%, Fe(OH)₃ content approximately 8%, Al(OH)₃ content approximately 30%) and mix it with 200 kg of lithium-containing waste aluminum electrolyte (lithium content approximately 2%). Add 150 kg of sulfuric acid (98%) and 500 kg of water, controlling the liquid-to-solid ratio at 3:1. The leaching temperature is 85℃, and the leaching is carried out with stirring for 4 hours. The final pH is 2.2. Filter to obtain lithium-containing leachate and lithium extraction residue. The lithium-containing leachate is purified and precipitated to obtain lithium carbonate product (purity 98.0%).

[0053] S2 (Secondary Defluorination and Fluorine Removal): The lithium extraction residue produced in step S1 is mixed with 500 kg of red mud and 100 kg of calcium oxide. 600 kg of fluoride-containing hydrochloric acid waste liquid is added, and the mixture is stirred and reacted for 2 h at a temperature of 80℃. The pH is adjusted to 7.0±0.3 with lime milk, and the mixture is filtered to obtain calcium fluoride precipitate (purity 96.2%) and defluorination mixture.

[0054] S3 (Preparation of coagulant through three acid leaching processes): The defluorinated mixture produced in step S2 was mixed with 300 kg of red mud and 80 kg of sulfuric acid. The mixture was heated to 90°C and aerated for 3 h at an aeration pressure of 0.6 MPa. The resulting composite coagulant solution was obtained by filtration. The Al2O3 content was determined to be 2.6 g / L, and the Fe2O3 content was 3.0 g / L.

[0055] Comparative Example 1 (Preparation of coagulant using traditional single red mud sulfuric acid process) The coagulant was prepared directly by reacting red mud with sulfuric acid, without staged lithium extraction or defluorination treatment. Specific steps: 600 kg of red mud was taken, 120 kg of concentrated sulfuric acid (98%) and an appropriate amount of water were added, the temperature was raised to 90℃, and the reaction was stirred for 3 h. The coagulant solution was obtained by filtration. The Al2O3 content was determined to be 2.2 g / L, and the Fe2O3 content was 2.5 g / L.

[0056] Comparative Example 2 (coagulant prepared by mixing different solid wastes after separate treatment) Aluminum electrolysis overhaul slag, red mud, and lithium iron phosphate extraction slag will be treated separately: Treatment of aluminum electrolysis overhaul slag: Take 500 kg of overhaul slag, add sulfuric acid for leaching, and filter to obtain filtrate A (Al2O3 1.5 g / L, Fe2O3 1.2 g / L). Red mud treatment: Take 400 kg of red mud, add 80 kg of concentrated sulfuric acid and water, stir for 3 h, and filter to obtain filtrate B (Al2O3 2.0 g / L, Fe2O3 2.3 g / L). Treatment of lithium iron phosphate residue: Take 200 kg of lithium residue, add sulfuric acid for leaching, and filter to obtain filtrate C (Al2O3 0.8 g / L, Fe2O3 3.5 g / L). Filtrates A, B, and C were mixed to obtain a mixed coagulant solution. After mixing, the Al2O3 content was 1.5 g / L and the Fe2O3 content was 2.4 g / L.

[0057] Comparative Example 3 (Lithium extraction directly from fluorinated hydrochloric acid, without pretreatment) 500 kg of the same aluminum electrolysis overhaul slag as in Example 1 was directly added to 800 kg of untreated fluorinated hydrochloric acid waste liquid (HF 5%), and the same leaching conditions were controlled (liquid-to-solid ratio 4:1, 80℃, 3 h). After filtration, the lithium concentration in the lithium-containing leachate was measured, and the lithium recovery rate was calculated to be only 52%. A large amount of LiF crystals were detected in the residue (confirmed by XRD analysis), indicating that fluoride ions reacted with lithium to form insoluble lithium fluoride precipitate, resulting in lithium loss. In contrast, Example 1, using pretreated low-fluoride hydrochloric acid, achieved a lithium recovery rate of 85%, demonstrating the necessity of pretreatment for fluoride removal.

[0058] Performance testing The coagulants prepared in Examples 1-3 and Comparative Examples 1-3, as well as commercially available polyaluminum chloride (PAC), were used to treat a dyeing and printing wastewater (initial turbidity 120 NTU, COD 850 mg / L, total phosphorus 5.2 mg / L). The dosage was calculated based on the total Al2O3+Fe2O3 content in the coagulant, which was 200 mg / L (i.e., 200 mg of coagulant containing Al2O3+Fe2O3 per liter of wastewater). Specific conversion: The required coagulant solution volume was calculated based on the Al2O3 and Fe2O3 concentrations measured in each example. For example, in Example 1, Al2O3+Fe2O3 = 6.0 g / L, then 33.3 mL of coagulant solution was required per liter of wastewater. All samples underwent coagulation tests under the same conditions: rapid stirring for 1 min (250 r / min), slow stirring for 15 min (50 r / min), and settling for 30 min before the supernatant was taken for analysis. The results are shown in Table 1.

[0059] Table 1. Effects of different coagulants on the treatment of dyeing and printing wastewater in the examples and comparative examples.

[0060] As shown in Table 1, Examples 1, 2, and 3, after introducing multi-source solid waste synergistic treatment, exhibited better coagulation performance than Comparative Example 1 (single red mud sulfuric acid method), Comparative Example 2 (mixing after separate treatment of each solid waste), and Comparative Example 3 (direct lithium extraction without pretreatment). Furthermore, they outperformed commercially available PAC in terms of COD removal rate and total phosphorus removal rate. The coagulation performance of Comparative Example 3 fell between that of Comparative Example 1 and Example 1, indicating that direct lithium extraction with untreated fluorinated hydrochloric acid not only resulted in low lithium recovery but also led to a slight decrease in the iron and aluminum content of the subsequent coagulant due to LiF precipitation entering the residue, thus affecting the coagulation effect. The multi-source synergistic treatment method of this invention has significant advantages in both lithium extraction efficiency and coagulation performance.

[0061] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste, characterized in that, Includes the following steps: S1, One-time leaching for lithium extraction: Low-fluoride hydrochloric acid or sulfuric acid is used to acidically leach lithium-containing solid waste, and the leaching solution and lithium extraction residue are obtained by filtration. S2, Secondary fluoride removal and fluoride extraction: The lithium extraction residue from step S1 is mixed and reacted with fluorine-containing materials and calcium source to precipitate and separate fluoride ions in the form of calcium fluoride. The mixture is then filtered to obtain calcium fluoride and fluoride removal solution. S3, preparation of coagulant by three acid leaching steps: the defluorinated mixture obtained in step S2 is mixed with iron and aluminum-containing solid waste, sulfuric acid is added, and the mixture is reacted under stirring and aeration conditions. The mixture is then filtered to obtain a composite coagulant solution.

2. The method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S1, the fluorine-containing hydrochloric acid waste liquid is reacted with a calcium source for pretreatment to obtain low-fluorine hydrochloric acid and calcium fluoride; the fluoride ion concentration in the obtained low-fluorine hydrochloric acid is ≤0.2 mol / L; the calcium source is one or both of calcium carbonate and calcium oxide materials.

3. The method for preparing composite coagulants through synergistic staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S1, the lithium-containing solid waste is one or more of the following: aluminum electrolysis overhaul slag, lithium-containing waste aluminum electrolyte, lithium extraction slag from lepidolite, waste lithium iron phosphate cathode material, and lepidolite neutralization and impurity removal slag.

4. The method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S1, during the acid leaching process, the leaching conditions are as follows: leaching liquid-to-solid ratio of 3:1 to 5:1, with the unit of liquid-to-solid ratio being L:kg; leaching temperature of 60 to 90°C; leaching time of 2 to 4 hours; and leaching endpoint pH of 1.5 to 2.

5.

5. The method for preparing composite coagulants through synergistic staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S2, the fluorine-containing material is one or more of the following: fluorine-containing hydrochloric acid waste liquid, aluminum electrolysis overhaul slag, and lithium-containing waste aluminum electrolyte; the calcium source is one or two of the following: calcium carbonate material and calcium oxide material.

6. The method for preparing composite coagulants through synergistic staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S2, at least one of the following is added to the mixing reaction: red mud, waste lithium iron phosphate lithium extraction slag, and lithium battery recycled iron-aluminum slag.

7. The method for preparing composite coagulants through synergistic, staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S2, during the mixing reaction, the reaction temperature is controlled at 60~90℃, the reaction time is 1~3 h, and the final pH is 6~8.

8. The method for preparing composite coagulants through synergistic staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S3, the iron-aluminum-containing solid waste is selected from one or more of the following: red mud, iron-aluminum slag from lithium battery recycling, lepidolite neutralization and impurity removal slag, and waste lithium iron phosphate lithium extraction slag. During the reaction process in step S3 under stirring and aeration conditions, the reaction temperature is 80~100℃, the reaction time is 2~5 h, and the aeration pressure is 0.2~0.6 MPa.

9. The method for preparing composite coagulants through synergistic staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: In step S1, the lithium-containing leachate is purified and precipitated to obtain lithium carbonate or lithium phosphate.

10. The method for preparing composite coagulants through synergistic staged extraction and cascade utilization of multi-source solid waste according to claim 1, characterized in that: The filter residue generated in each step is washed with water and then used for building materials or landfill. The washing liquid obtained after washing the filter residue is recycled to step S1 or step S3. When recycling, the concentration of fluoride ions in the washing liquid is controlled to not exceed 0.5 g / L.

Citation Information

Patent Citations

  • High-iron red mud and waste cathode coprocessing resourceful utilization method

    CN109487078A

  • Carbon reduction and emission reduction type combined recovery method for waste lithium iron phosphate and iron-aluminum slag

    CN118833787A